The effect of regulation and goal orientation on performance measurement utilisation: evidence from Indonesian local government - ., Nurkholis; Mohamad, Muslim Har Sani; Ismail, Suhaiza (University of Malaya, 2014)
This study examines how regulation on performance measurement and goal orientation affect the utilisation of performance measurement in the context of a developing country’s local governments. This study is based on a cross-sectional survey participated by 163 manager of local government agencies managers in East Java, Indonesia, using a structural approach in data analysis. The results show that the imposition of regulation on performance measurement directly affects performance measurement adoption. The adoption of performance measurement and goal orientation mediate the relation between the regulation and the actual implementation of performance measurement. The likelihood of the actual implementation of performance measurement becomes stronger when there is strong goal orientation. The unique contribution of this study is that it offers a model of regulatory-based performance measurement utilisation under result-based management from a developing country perspective, depicting that imposed regulation on performance measurement will likely lead to its actual implementation when there is strong goal orientation.